La influencia de la ansiedad: la presencia vitalicia de Rubén Darío en la obra de César Vallejo - Feinstein, Adam (2022)
Harold Bloom established the concept of the «anxiety of influence», that is, the phenomenon whereby the author has the need to escape the influence of a predecessor and promotes, in itself, a coloring of the later writer’s work. In this article, we examine what we call instead the «impact of anxiety». It is argued that this phenomenon could be found in the mark that the Nicaraguan modernist, Rubén Darío, left on the work of César Vallejo, and that, contrary to what is generally assumed, this impression was, in fact, lifelong, rather than just hovering in the poet’s first collection of poems, Los heraldos negros.